Spectrum Changes Produced by Scattering of Light With Tunable Spectral Degree of Coherence from a Spatially Deterministic Medium - Jia Li; Pinghui Wu; Yali Qin; Shuqin Guo (IEEE Photonics Journal, 2016)
Within the validity of the first-order Born approximation, we study the spectrum changes generated by the scattering of light with a tunable spectral degree of coherence (SDOC) from a spatially deterministic medium. Before interacting with the medium, a scalar plane wave is incident upon Young's pinholes, which are employed to produce the incident wave with a tunable SDOC. By assuming that both the scattering potential of the medium and the spectrum of incident plane waves obey Gaussian profiles, the spectrum of the scattered field is derived as a linear combination of Fourier transforms of the scattering potentials. Changes in the spectrum of the scattered field are strongly dependent on the scattering angle, the effective radius of the medium, and Young's pinhole parameter. Moreover, red shifts occurring in the scattered field can be enhanced by either reducing the scattering angle or increasing the effective radius. The results presented here generalize the previous reports, where the light with prescribed functions of the SDOC scattered from a deterministic medium was considered.